This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's some pretty amazing gymnastics.
Thanks. I have changed the solution.
How can anyone ever think of such solution...
Let a = cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π and b = cos 1 3 4 π + cos 1 3 1 0 π + cos 1 3 1 2 π .
Also, let w = e 1 3 2 π i , so using w k + w 1 3 − k = 2 cos ( 1 3 2 π k ) , we get:
a = 2 w + w 1 2 + w 3 + w 1 0 + w 4 + w 9 b = 2 w 2 + w 1 1 + w 5 + w 8 + w 6 + w 7 .
Then, try to find a + b and a b , the first was easy using w + w 2 + w 3 + ⋯ + w 1 2 = − 1 , which follows inmediatly from factoring w 1 3 = 1 :
a + b = − 2 1
But to find a b let's find the whole product and use the fact that w 1 3 = 1 , we end with a b = − 4 3 .
Finally, by the fact that a > 0 and b < 0 , use Vieta's formulas to find that a = 4 − 1 + 1 3 and b = 4 − 1 − 1 3 .
So, cos ( 1 3 2 π ) + cos ( 1 3 6 π ) + cos ( 1 3 8 π ) = 4 − 1 + 1 3
On comparing we get α = 1 3 , β = 1 , γ = 4 , thus the final answer is 1 3 + 1 + 4 = 1 8 .
This problem has been previously posted.
Problem Loading...
Note Loading...
Set Loading...
Since z 1 3 = e 1 3 2 π i = 1 are the 13 t h roots of unity. By Argand's diagram, we can see that:
cos 1 3 2 π + cos 1 3 4 π + cos 1 3 6 π + cos 1 3 8 π + cos 1 3 1 0 π + cos 1 3 1 2 π = − 2 1 cos 1 3 2 π + 2 cos 2 1 3 2 π − 1 + cos 1 3 6 π + cos 1 3 8 π + 2 cos 2 1 3 5 π − 1 + 2 cos 2 1 3 6 π − 1 = − 2 1 cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π + 2 ( cos 2 1 3 2 π + cos 2 1 3 6 π + cos 2 1 3 8 π ) − 3 = − 2 1 cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π + 2 ( cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π ) 2 − 4 ( cos 1 3 2 π cos 1 3 6 π + cos 1 3 2 π cos 1 3 8 π + cos 1 3 6 π cos 1 3 8 π ) = 2 5 [ Note 1 ] cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π + 2 ( cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π ) 2 − 4 ( − 4 1 ) = 2 5 2 ( cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π ) 2 + cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π − 2 3 = 0 4 ( cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π ) 2 + 2 ( cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π ) − 3 = 0
⇒ cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π = 8 − 2 ± 4 + 4 8 = 4 1 3 − 1 [ Note 2 ]
⇒ a + b + c = 1 3 + 1 + 4 = 1 8
Note 1: See solution of Part 2 .
Note 2: cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π = cos 1 3 2 π + cos 1 3 6 π − cos 1 3 5 π . We know that cos 1 3 2 π > cos 1 3 5 π > cos 1 3 6 π > 0 ⇒ cos 1 3 2 π + cos 1 3 6 π + cos 1 3 8 π > 0 .